1992
DOI: 10.1007/bf01990963
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory action of ethanol on the gastric mucosa and its interaction with the vagus in rats

Abstract: The influence of systemic ethanol and/or the vagus on ionic secretion and on glandular mucosal blood flow (GMBF) was studied in an ex-vivo gastric chamber preparation in rats. Sub-diaphragmatic vagotomy decreased H+ secretion and Na+ outflux from the gastric mucosa. Subcutaneous injection of 50% ethanol significantly potentiated these responses, but not the concentrations of 25% and 100%. The three doses of ethanol did not affect the secretion of both H+ and Na+ in vagus-intact animals. Ethanol, however dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This could reduce the ion transport and acid secretion. Indeed, parenteral injection of ethanol inhibits gastric Na + and H + output [5]. Thus, in addition to the local damaging action on the epithelial mucosa by the alcohol, it is likely that systemic ethanol can also adversely affect stomachs, at least in part through electrophysiological interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could reduce the ion transport and acid secretion. Indeed, parenteral injection of ethanol inhibits gastric Na + and H + output [5]. Thus, in addition to the local damaging action on the epithelial mucosa by the alcohol, it is likely that systemic ethanol can also adversely affect stomachs, at least in part through electrophysiological interference.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations are focused on studying the ulcerogenesis [1][2][3], acid secretion [4][5][6] and electrophysiology [7][8][9] in whole animals. However, the actions of ethanol are complicated by the interactions with the neurohormonal changes and gastric mucosal blood flow, and therefore discrepancies have been reported among these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The states of ionic fluxes are used as indicator for the integrity of the epithelium [32], Previous studies had demonstrated that gastric mucosal damaging agents, such as ethanol and bile salts, inhibited the active transport of sodium in oxyntic mucosa of canine and rat stomachs [33][34][35]. In the present ex vivo study, the basal secretion of sodium ions from the mucosa into the gastric lumen was significantly elevated by the pretreatment of 5% NaCl and 0.3 M HC1, in addition to the prevention of the 100% ethanol-induced drop in ionic secretory function by all three mild irritants.…”
Section: Discussionmentioning
confidence: 99%
“…Copenhagen). The Na* content was measured by an ion meter (model ION83 Radiometer, Copenhagen) with a coefficient of variation of less than 5% [10]. Pepsin activity in the incubation solution was deter mined by the method of Berstad [14],…”
Section: Measurements O F H* Na* and Pepsin Secretionmentioning
confidence: 99%
“…Ondansetron, a selective 5-HT3 receptor antagonist [8], competitively blocks the depolarizing effects of 5-HT in the isolated rat vagus nerve [9]; the blocking of which has been shown to affect gastric function and ethanol-induced gastric damage in intact animals [10,11]. It is envis aged that 5-HT3 receptors could play a modu latory role in the physiological and pathologi cal changes in the stomach.…”
Section: Introductionmentioning
confidence: 99%